2019
DOI: 10.1038/s41598-019-53706-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Colorectal Cancer Radiation Therapy Efficacy using Silver Nanoprisms Decorated with Graphene as Radiosensitizers

Abstract: Metal nanoparticles have significant interaction cross-sections with electromagnetic waves due to their large surface area-to-volume ratio, which can be exploited in cancer radiotherapy to locally enhance the radiation dose deposition in tumors. We developed a new type of silver nanoparticle composite, PEGylated graphene quantum dot (GQD)-decorated Silver Nanoprisms (pGAgNPs), that show excellent in vitro intracellular uptake and radiosensitization in radiation-sensitive HCT116 and relatively radiation-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Habiba et al reported that HT29 tumor cells were radiation-resistant up to 4 Gy when exposed to GO-silver nanoparticles, whereas the survival fraction was reduced by or to 10% at 6 Gy, along with DNA damage. Our work and Habiba et al’s study confirms the radiosensitization of GO-based nanomaterials [ 54 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Habiba et al reported that HT29 tumor cells were radiation-resistant up to 4 Gy when exposed to GO-silver nanoparticles, whereas the survival fraction was reduced by or to 10% at 6 Gy, along with DNA damage. Our work and Habiba et al’s study confirms the radiosensitization of GO-based nanomaterials [ 54 ].…”
Section: Resultssupporting
confidence: 89%
“…These results confirmed that, under these dosages, the cell apoptosis was mainly due to photon radiation effect and independent of GO presence. When increasing the photon dose to 6 Gy or 8 Gy, the NPC-BM1 cells without GO showed 15–19% cell apoptosis under the radiation influence [ 54 , 55 ]. At these high radiation dosages (6–8 Gy), the GO-treated sample exhibited increased mortality rate to 26–27%.…”
Section: Resultsmentioning
confidence: 99%
“…The exact action mechanism varies depending on the physical and chemical properties of the nanoparticle and the type of cancer [5]. Furthermore, the clinical use of colloidal silver for bactericidal and antiviral purposes proves that this treatment is safe [6,7].…”
Section: Introductionmentioning
confidence: 99%
“… 46 Furthermore, graphene decorated TAgNPs also resist degradation following cell uptake and were shown to be effective radiation sensitizers. 22 Whether other types of TAgNPs with greater stability offer an advantage over those used in this study remains to be determined. Under conditions typically used for photothermal therapy, the combined bulk heating of nanoparticles dispersed across the tumor volume, including those in the extracellular space, produces a global temperature rise orders of magnitude larger than the localized temperature rise near each particle.…”
Section: Discussionmentioning
confidence: 97%